Sustainable Chromium Encapsulation: Alkali Activation Route - Sgarlata, Caterina; Leonelli, Cristina; Lancellotti, Isabella; Mortalò, Cecilia; Berrettoni, Mario; Fattobene, Martina; Zamponi, Silvia; Giorgetti, Marco (Frontiers in Materials, 2022)
This article highlights recent experimental advances in the use of inorganic substances in the encapsulation of pollutants and, in particular, discusses the potential applicability and constraints of the geopolymerization process for the treatment of wastewater containing Cr(III). A great percentage of waste containing chromium salts is produced by the leather industry during the tannery process. Such industrial waste is in the form of liquor containing almost 40% of the initial chromium combined with many other pollutants. The stabilization/solidification (S/S) treatment of this type of waste must be combined with chromium encapsulation in an economic, environmentally friendly and efficient process to be industrially feasible. Here we present a novel process in which the wastewater is used as a component of the formulation together with a clay by-product and with the addition of NaOH pellets with the goal of a no-water plus no-waste technology approach. The final solidified “ceramic-like” material successfully immobilized the heavy metal cations as well as anions and macromolecules of surfactants, avoiding environmental damages to soil and groundwater. The article is completed by mentioning other S/S processes where wastewater has been treated and the resulting sludge encapsulated. The future of the S/S technologies in the tannery industry should progress in the direction of significantly reducing the amount of wastewater directed to the treatment plants, with associated reductions in transport and their CO2 emissions. This article intends to be a contribution in the direction of preventing waste, aligning circular economy and waste management objectives.